2022
DOI: 10.1002/rfe.1154
|View full text |Cite
|
Sign up to set email alerts
|

The co‐movements of faith‐based cryptocurrencies in periods of pandemics

Abstract: In the recent coronavirus pandemic, several researchers have focused on the drivers of cryptocurrency behavior. In particular, this study provides insights into what can drive Islamic cryptocurrency markets and how do they react during the COVID‐19 pandemic. We explore the cryptocurrency volatility and the connectedness between the Islamic, conventional, and COVID‐19 confirmed cases and deaths using the wavelet approaches. The preliminary results show that faith‐based cryptocurrencies have reduced risk exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Recently, Rufino (2023) confirmed that Bitcoin market efficiency deteriorated during the pandemic period. This is supported by Mnif et al (2023), who also reported that during unexpected events such as the Russia-Ukraine war, the Bitcoin market inefficiency increases. However, Chowdhury et al (2023) noticed that during the Covid-19 period, the market efficiency of the S&P 500 changed more than did that of Bitcoin.…”
Section: Literature Reviewmentioning
confidence: 66%
See 1 more Smart Citation
“…Recently, Rufino (2023) confirmed that Bitcoin market efficiency deteriorated during the pandemic period. This is supported by Mnif et al (2023), who also reported that during unexpected events such as the Russia-Ukraine war, the Bitcoin market inefficiency increases. However, Chowdhury et al (2023) noticed that during the Covid-19 period, the market efficiency of the S&P 500 changed more than did that of Bitcoin.…”
Section: Literature Reviewmentioning
confidence: 66%
“…Thirdly, this paper contributes to the literature on the dynamics of Bitcoin market efficiency and its potential factors. Despite many recent studies on the dynamics of Bitcoin market efficiency, there is no comprehensive evidence on whether the dynamics of Bitcoin market efficiency are related to uncertainty (Wang et al, 2021;Diniz-Maganini et al, 2021;Mensi et al 2022;Phiri, 2022;Fernandes et al, 2022;Mnif, Mouakhar & Jarboui, 2023). In addition, so far it has not been verified in the context of emerging stock markets.…”
Section: Introductionmentioning
confidence: 98%
“…In other words, these Islamic inventions, unlike conventional cryptocurrencies, contain tangible financial factors that underpin their pricing. As a result, their volatility and speculation are limited by these qualities (Berentsen and Schär 2018;Mnif et al 2022). Stellar is the first distributed ledger protocol to achieve Sharia compliance from the Shariah Review Board licensed by the Central Bank of Bahrain in the money transfer and asset tokenization space.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that some studies discuss the interaction between Islamic metalbacked cryptocurrencies and conventional cryptocurrencies, and the potential for cryptocurrencies to become more suitable for Islamic finance (Abubakar et al 2019;Alam et al 2019;Ayedh et al 2020;Houssem and Robbana 2019;Kakkattil 2019;Yousaf and Yarovaya 2022), this paper is motivated by some gaps in the literature. Firstly, as a purely cryptographic asset, Bitcoin can be transacted and used effectively as a method of payment, however, it does not seem to be universally accepted by Islamic (faith-based) retailers or investors looking for opportunities and businesses that adhere to Shariah (Mnif et al 2022). It is pertinent to consider using a powerful tool based on modern financial technology to satisfy the demand for Islamic financial instruments and contracts, which would not only be compatible with Islamic Shariah laws but also be accepted in global financial transactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation